2013
DOI: 10.1159/000350070
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Toxin Suppresses Expression of Ubiquitin Editing Enzyme A20 and Enhances Transcytosis

Abstract: Background: The ubiquitin editing enzyme A20 plays an important role in maintaining the homeostasis in the body Microbe-derived adjuvants are commonly used in animal models of intestinal allergy. Objective: This study aims to investigate the role of cholera toxin-induced A20 suppression in compromising intestinal barrier function. Methods: Human intestinal epithelial cells were cultured into monolayers as an in vitro epithelial barrier model. Ovalbumin (OVA) was used as a specific allergen to test the degradin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…Cumulative evidence shows incompetent of epithelial cells in the degradation of the endocytic proteins under given circumstances (Huang et al, ; Li et al, ; Liao et al, ) that results in epithelial barrier dysfunction. We considered whether additional avb6 facilitates the degradation of the endocytic antigens under circumstances such as in high levels of proinflammatory cytokines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulative evidence shows incompetent of epithelial cells in the degradation of the endocytic proteins under given circumstances (Huang et al, ; Li et al, ; Liao et al, ) that results in epithelial barrier dysfunction. We considered whether additional avb6 facilitates the degradation of the endocytic antigens under circumstances such as in high levels of proinflammatory cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…The epithelial barrier dysfunction occurs when macromolecular molecules, such as protein antigens, fail to pass through the epithelial barrier to arrive at the deep tissues of the body, such as the subepithelial region, where the antigens may contact various immune cells and initiate aberrant immune responses and immune inflammation. A number of factors are recognized associating with epithelial barrier dysfunction, including psychological stress (Zheng et al, ; Yu et al, ), exposure to microbial products (Li et al, ; Liu et al, ), allergy (Rezaee et al, ; Liu et al, ; Post et al, ) and chronic inflammation (Gersemann et al, ). To date, the underlying mechanism of epithelial barrier dysfunction is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial cells express CD23 on the surface that facilitates the transcellular transport of specific antigens across the epithelial barrier [12,13]. Recent reports indicate that exposure to microbial products also affects the epithelial barrier functions [5,8]. The present study adds novel information to this area by showing that Alix is required in the maintenance of the epithelial barrier function.…”
Section: Discussionmentioning
confidence: 61%
“…Under healthy condition, epithelial cells endocytose some proteins of small molecular weight; those endocytic cargo can be wrapped by the plasma membranes to be formed as endosomes; the latter fuse with lysososmes where there are acidic enzymes to degrade the endocytic cargo. Recent reports indicate that there are a number of factors can affect the endolysosome systems to enhance the epithelial barrier permeability [5-7]; the causative factors include microbial products, such as cholera toxin [5] and SEB [8]. The underlying mechanism remains to be further understood.…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency of A20 promoted intestinal allergy [14]. Li et al observed that exposure to cholera toxin suppressed the expression of A20, which resulted in compromising epithelial barrier function [27]. Vereecke et al found that deficiency of A20 promoted the development of colitis in mice [28].…”
Section: Discussionmentioning
confidence: 99%